An exploration of ancient yoga in Bali: An effort to make Bali a world centre for spiritual tourism - Widana, I Ketut Arta; Sudiana, I Gusti Ngurah; Widyastuti, Ni Putu (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Background: Religion is often considered as a cause of environmental problems. In response to this pessimism, Buddhism through the philosophy of Dharma comes up as revolutionary perspective in shaping contemporary environmental development paradigm, a counter for modern Cartesian-Newtonian paradigm. This philosophy is embodied in the concept of paṭiccasamuppāda applied as “scalpel” on existing environmental problems. Methods: This research uses a qualitative case study to explore the revival of Ancient Balinese Yoga as a spiritual tourism destination. Data were collected through interviews, observations, document analysis, and FGDs. Data analysis included transcription, coding, thematic analysis, and contextual interpretation, with triangulation to validate findings. Findings: Currently, there are significant efforts to revive Ancient Balinese Yoga as a spiritual tourism destination in Bali. Especially with the increasing of global interest in wellness and spirituality, Bali has great potential to attract tourists seeking authentic spiritual experiences. This involves the restoration and revitalization of traditional practices, including the hosting of yoga retreats, spiritual training, and festivals featuring ancient aspects of Balinese yoga and meditation. The development of spiritual tourism based on Ancient Balinese Yoga focuses on maintaining the authenticity of the practice while adapting to the needs and expectations of modern tourists. Conclusion: By combining yoga training with cultural tours, spiritual seminars, and meditation programs, Bali can position itself as a major hub for global spiritual tourism. Reviving Ancient Balinese Yoga as a spiritual tourism destination also supports the preservation of Bali's cultural and spiritual heritage, provides economic benefits to local communities, and enriches the traveler’s experience with authentic spiritual depth. Novelty/Originality of this article: By bridging Buddhist philosophy with the revival of Ancient Balinese Yoga, this research offers a novel perspective on addressing contemporary ecological challenges, highlighting the interconnectedness of all life and proposing spiritual practices as essential components of sustainable development.